(3OQGSI GSJWdGYjI Mhd UfGYI GdEYdGejGJ aj GdhWf GdYQHj (B. /s - (3GdefXeI GdYQHjI ddJQHjI h GdKbGaI h GdYdhe EOGQI GdYdhe s ((3JhfS (B:s (3GdefXeI GdYQHjI ddJQHjI h GdKbGaI h GdYdhe ,s, 1990)
(3Ef QSGdI GdefXeI GdYQHjI ddJQHjI h GdKbGaI h GdYdhe aj LYd GddZI GdYQHjI hYGA ddYdhe Edi YUQ GdJcfhdhLjG hhSjdI dfbd CeJfG GdYQHjI Edi YUQ GdJcfhdhLjG GdeJbOeI (B,(3bO OaY GdefXeI GdYQHjI aj hbJ eHcQ Edi GdGgJeGe HGdGYdGejGJ ef MjK GSJNOGeGJgG h JOQjH GdCWQ aj eSGbGJgG GdeNJdaI (B.(3h JCJj gPg GdOQGSI GdJj CYOgG NHjQ GdGYdGejGJ GdGSJGP GdOcJhQ efPQ UdGM HJcdja ef GdefXeI eSGgeI efgG aj JSdjW GdCVhGA Ydi hGbY GdbOQGJ GdhWfjI h GdbhejI aj eLGd JcfhdhLjG GdGYdGejGJ HZjI JYRjR GdYed GdYQHj GdeTJQc aj gPG GdeLGd GdgGe (B. s
Keywords: (3GdEYdGes; (3GdhWf GdYQHjs